Initial Displacement Does Not Affect Loss of Reduction After Lisfranc Fracture Dislocations. Issue 6 (December 2019) - Pigott, Matthew T.; Shah, Ronit; Chan, Jason; Irwin, Todd A.; Holmes, James R.; Talusan, Paul G.
We sought to determine whether significantly displaced Lisfranc injuries had a higher rate of loss of reduction after fixation compared to those with low displacement. Forty-five patients who had fixation of an acute Lisfranc injury from 2005 to 2014 were retrospectively reviewed. All patients underwent subsequent hardware removal at 3 to 15 months after their index procedure. Radiographs were reviewed from the time of injury, 2 weeks, and 6 months postoperative. Lisfranc joint reduction was assessed using criteria previously described in the literature and graded as malreduced if displacement was >2 mm. We used a cutoff of 4 mm for high initial displacement. Those patients with ≥4 mm of initial displacement did not have an increased rate of loss of reduction after hardware removal compared to those patients with <4 mm initial displacement (40% and 27%, respectively; P = .362). Anatomic reduction was achieved immediately postoperative in 89% of cases. A high degree of displacement in Lisfranc injuries does not preclude achievement and maintenance of adequate reduction after fixation of these injuries. Levels of Evidence: Prognostic study, Level II: Retrospective